Interactive effects of temperature and nitrogen on the physiology of kelps (Nereocystis luetkeana and Saccharina latissima) - Fales, Robin J.; Weigel, Brooke L.; Carrington, Emily; Berry, Helen D.; Dethier, Megan N. (Frontiers in Marine Science, 2023)
Kelp forest declines have been linked to warming ocean temperatures worldwide. Ocean warming rarely occurs in isolation, so multiple stressor studies are necessary to understand the physiological responses of kelp to climate change. The canopy-forming bull kelp, Nereocystis luetkeana, is going locally extinct in areas of the Salish Sea that are seasonally warm and nutrient poor, while the understory kelp, Saccharina latissima, persists at those sites. Further, nitrogen availability can alter physiological responses of kelps to temperature stress, including alleviating warming stress. We compared the physiological responses of kelp sporophytes to high temperature stress and nitrogen limitation between two populations of N. luetkeana with different environmental histories (warm and nutrient poor vs. cold and nutrient rich) and between two species, N. luetkeana and S. latissima. Using laboratory mesocosms, we tested the interactive effects of short term (8-9 day) exposure of kelp blades to different temperatures: low (9, 13°C), moderate (15, 16°C), and warm (21°C) at two different nitrogen concentrations: low (1-3 μM) vs. high (>10 μM). We examined a wide array of physiological responses: blade growth, photosynthesis, respiration, photosynthetic yield, nutrient uptake, and tissue C:N. Both kelp species responded negatively to elevated temperatures, but not to low nitrogen levels. Blades of both species showed signs of metabolic stress and reduced growth in the warmest temperature treatment (21°C), at both high and low nitrogen levels, suggesting that N. luetkeana and S. latissima are susceptible to thermal stress over short time periods. Populations of N. luetkeana from warm, nutrient poor and cool, nutrient rich areas were equally susceptible to the effects of ocean warming. Our results suggest that nutrient additions may actually reduce kelp performance at supra-optimal temperatures, and a thorough understanding of kelp responses to coastal temperature and nutrient dynamics is needed to guide conservation and restoration actions.